Surgical treatment of uveal melanoma: Exoresection versus endoresection - Seung Min Lee; Min Kim (Taiwan Journal of Ophthalmology)
Uveal melanoma, the most common primary intraocular malignancy in adults, presents significant therapeutic challenges. With the advancement of surgical instruments and techniques, exoresection (ab-externo) and endoresection (ab-interno) have emerged as viable treatment methods. These surgical interventions can be implemented particularly for tumors exceeding traditional size criteria for plaque brachytherapy and for tumors that are too large, which pose an elevated risk of radiation-related complications. Moreover, surgical interventions not only enhance the potential for functional vision preservation and globe retention but also provide effective control of intraocular tumors and metastatic disease when combined with adjunctive radiation therapy. Exoresection, an external approach, involves dissection and removal of the tumor through a scleral flap, while endoresection utilizes vitreoretinal surgical techniques for internal tumor excision. Both surgical techniques for uveal melanoma removal are highly challenging, carry significant risks of complications, and should be performed by experienced vitreoretinal surgeons specializing in ocular oncology at specialized centers. They aim to preserve the eye and potentially maintain useful vision while saving patients’ lives, a crucial consideration in ocular oncology. These surgical modalities have become increasingly relevant as the field progresses towards more conservative, function-preserving approaches in cancer treatment. The aim of this article is to conduct a comparative analysis of exoresection and endoresection in the context of uveal melanoma management. By critically evaluating these surgical modalities, this review seeks to provide clinicians with valuable insights to guide treatment decisions for patients with large uveal melanomas.